Management Fisioterapi pada Kasus Fraktur Femur 1/3 Distal Dextra di Rumah Sakit PKU Muhammadiyah Yogyakarta : Case Report - Nabilla Windi Aulia; Galih Adhi Isak Setiawan; Wahyu Tri Sudaryanto (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
Femur fracture is a condition where there is discontinuity or loss of part of the femur bone, To overcome this, physiotherapy can contribute to reducing pain, reducing edema, increasing joint range of motion, and strengthening muscles. Objectives: physiotherapy can contribute to reducing pain, reducing edema, increasing joint range of motion, and strengthening muscles. Physiotherapy modalities that are often used for this condition include Transcutaneous Electrical Nerve Stimulation (TENS), Ultrasound, and exercise. Results: after 6 times of therapy, a decrease in tenderness T1:5 and T6: 4, motion pain T1: 7 and T6: 2. ROM knee extension/flexion T1: S: 5°-0°-40°, T6: S: 0°-0°-100°. Conclusion: Administration of TENS, ultrasound and exercise can reduce pain, increase ROM in post fracture of 1/3 Distal femur.